Hadith #2783 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Beware of the wages of a distributor of booty (qusamah). We asked: What is qusamah (wages of a distributor)? He said: It means a thing which is shared by the people, and then it is reduced.
Grade: Da'if

Hadith #3169 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Walid bin Shuja' bin al-Sakuni الوليد بن شجاع بن الوليد بن قيس السكوني; ibn Abbas; Karayb bin Abi Muslim كريب بن أبي مسلم الهاشمي; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر (Sunan Abi Dawud)
‘Abd Allah b.’Umar dont you hear what Abu Hurairah says ? He heard the Messenger of Allah (ﷺ) say: If anyone goes out of his house, accompanies bier and prays over it…. He then mentioned the rest of the tradition as narrated by Sufyan. Thereupon Ibn ‘Umar sent someone to ‘Aishah (asking her about it). She replied: Abu Hurairah spoke the truth.
Grade: Sahih

Hadith #3343 - Sunan Abi Dawud - ibn Abbas; Ikrama عكرمة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Uthman bin Muhammad; Uthman ibn 'Affaan; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) would not say funeral prayer over a person who died while the debt was due from him. A dead Muslim was brought to him and he asked: Is there any debt due from him? They (the people) said: Yes, two dirhams. He said: Pray yourselves over your companion. Then AbuQatadah al-Ansari said: I shall pay them, Messenger of Allah. The Messenger of Allah (ﷺ) then prayed over him. When Allah granted conquests to the Messenger of Allah (ﷺ), he said: I am nearer to every believ
Grade: Sahih

Hadith #3561 - Sunan Abi Dawud - Abdul 'Aziz bin Rafi' عبد العزيز بن رفيع; al-Hasan bin Muhammad al-Za'farani الحسن بن محمد الصباح الزعفراني; Safwan bin Umayyah; Salmah bin Shbyb سلمة بن شبيب; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Umayya bin Safwan bin Umayyah أمية بن صفوان بن أمية الجمحي; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: The hand which takes is responsible till it pays. Then al-Hasan forgot and said: (If you give something on loan to a man), he is your depositor ; there is no compensation (for it) on him.
Grade: Da'if

Hadith #3699 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Amr bin al-Aswad al-Ansi عمرو بن الأسود العنسي; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Ziyad bin Fyad al-Khza'y زياد بن فياض الخزاعي (Sunan Abi Dawud)
When the Messenger of Allah(ﷺ) forbade the use of(wine) vessels, Ansar said: They are inevitable for us. Thereupon he said: If so, then no
Grade: Sahih

Hadith #3827 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade these two plants (i.e. garlic and onions), and he said: He who eats them should not come near our mosque. If it is necessary to eat them, make them dead by cooking, that is, onions and garlic.
Grade: Sahih

Hadith #3888 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; al-'Abbas ibn 'Abd al-Muttalib; Amir al-Sha'bi عامر الشعبي; Anas ibn Malik; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
I passed by a river. I entered it and took a bath in it. When I came out, I had fever. The Messenger of Allah (ﷺ) was informed about it. He said: Ask AbuThabit to seek refuge in Allah from that I asked: O my Lord, will the spell be useful? He replied: No, the spell is to be used except for the evil eye or a snake bite or a scorpion sting. Abu Dawud said: Humah means the biting of snakes and sting of the poisonous insects.
Grade: Hasan

Hadith #4028 - Sunan Abi Dawud - ibn Umar; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Uthman bin Abi Zr'h Mwla عثمان بن أبي زرعة; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) distributed outer garments with full-length sleeves but did not give Makhramah anything. Makhramah said: Go with us to the Messenger of Allah (ﷺ). So I went with him and he said: Enter and call him for me. I then called him. He came out to him and he had an outer garment with full-length sleeves over him from those garments. He said: I kept it for you. He looked at it, meaning Makhramah according to the addition of Ibn Mawhab. The agreed version then says: He said:
Grade: Sahih

Hadith #4170 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sa'id bin Jubayr سعيد بن جبير الأسدي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر (Sunan Abi Dawud)
The woman who supplies fake hair and the one who asks for it, the woman who pulls out hair for other people and the woman who depilates herself, the woman who tattoos and the one who has it done when there is no disease to justify it have been cursed. Abu Dawud said: Wasilah means the woman who adds false hair to the hair of women. Mustawsilah means the one who asks for adding the hair to her hair. namisah means a woman who plucks hair from the brow until she makes it thin; mutanammisah means th
Grade: Sahih

Hadith #4225 - Sunan Abi Dawud - Abdullah bin Hnyn عبد الله بن حنين الهاشمي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ali ibn Abi Talib; Ibrahim bin 'Abdullah إبراهيم بن عبد الله بن حنين; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to me: Say: O Allah, guide me, and set me right. Remember by guidance (hidayah) the showing of the straight path, and remember by setting right (sadad) the setting right of an arrow. Then pointing to the middle finger and the one next to it, he said: He forbade me to wear a signet-ring on this finger of mine or on this (Asim was doubtful). He forbade me to wear qassiyyah (qasi garments) and mitharah. Abu Burdah said: We asked ‘Ali: What is qasiyyah ? He said:
Grade: Sahih

Hadith #4643 - Sunan Abi Dawud - Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Qtn bin Nsyr قطن بن نسير; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
I heard al-Hajjaj say on the pulpit: Fear Allah as much as possible; there is no exception in it. Hear and obey the Commander of the Faithful ‘Abd al-Malik; there is no exception in it. I swear by Allah, if order people to come but from a certain gate of the mosque, and they come out from another gate, their blood and their properties will be lawful for me. I swear by Allah, if I seize the tribe of Rabi’ah for the tribe of Mudar, it is lawful for me from Allah. Who will apologies to me for t
Grade: Hasan

Hadith #4806 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Mqdam bin Shryh bin Han'i المقدام بن شريح بن هانئ بن يزيد; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Sharih bin Hani' al-Harithi شريح بن هانئ; Uthman ibn 'Affaan (Sunan Abi Dawud)
I went with a deputation of Banu Amir to the apostle of Allah (ﷺ), and we said: You are our lord (sayyid). To this he replied: The lord is Allah, the Blessed and Exalted. Then we said: And the one of us most endowed with excellence and superiority. To this he replied: Say what you have to say, or part of what you have to say, and do not let the devil make you his agents.
Grade: Sahih